Ralph Compton the Sagebrush trail : a Ralph Compton western - Compton, Ralph; Randisi, Robert J. (Compton, Ralph. Trail drive series., 2021)
"Capturing and breaking wild horses is a tough way to make a living, but Montana ranch owner Ethan Miller's problems are just getting started. When his buyer falls through, the only other market he can find for his herd is the US Cavalry. But that means driving two hundred horses all the way from Bozeman, Montana, to Fort Davis, Texas. No sooner has he complete the dangerous trek than he's issued an ultimatum. A shipment of rifles and ammunition has gone missing, the Fort commander has plenty of men to go out searching for the weapons, but no scout. So if Ethan hopes to get paid, he will be expected to use all his skills and years of scouting experience for one deadly mission. . . ."--Back cover.